Reporting the Road to Brexit International Media and the EU Referendum 2016 (Cham : Springer International Publishing, 2018)
This edited collection brings together leading international scholars to explore the connection between Brexit and the media. The referendum and the activism on both sides of the campaign have been of significant interest to the media in the UK and around the world. How these factors have been represented in the media and the role of the media in constructing the referendum narrative are central to assisting the development in our understanding of how UK and global democracy is being manifested in contemporary times. This book explores these topics through presenting a wide range of perspectives from research conducted by leading international scholars, and concludes with an assessment of the potential democratic and international implications for the future. By grappling with a highly important and controversial topic in a comparative and varied way, the volume contributes to theoretical debates about the nature and role of the media in complex social, political and cultural contexts.
1. Introduction, Anthony Ridge-Newman,Fernando León-Solis, Hugh O'Donnell -- 2. Polarised Politics and Personalisation: Coverage of the EU referendum on British TV News, Andrew Tolson -- 3. Mobilizing Migration: analyzing the role of the 'migrant' in the British press during the EU referendum debate [UK and Commonwealth], Oisín Share -- 4. Scotland, Wales and press discourses amid the 2016 EU Referendum, Michael Higgins -- 5. The EU Referendum on Scottish television, Marina Dekavalla -- 6. Whither the 'hand of history': Northern Ireland newspaper coverage of the EU referendum campaign, Stephen Baker -- 7. 'A pit we have dug ourselves': Brexit and the Welsh democratic deficit, Simon Gwyn Roberts -- 8. The EU referendum in Gibraltar: an analysis of opinion articles from Gibraltarian newspapers, Ángela Alameda Hernández -- 9. Left versus right, or mainstream versus margins? Divisions in French media reactions to the Brexit vote, Thomas Martin and Laurent Binet -- 10. The EU Referendum Stories in Austrian, German, and Swiss Media: Catastrophes, Characterisations, Challenges, Klaus Peter Müller -- 11. The Media Coverage of the EU Referendum in Spain, Fernando León-Solís, Enric Castelló, Hugh O'Donnell -- 12. 'Little England beats Great Britain': Italian Media Coverage of Brexit, Rinella Cere -- 13. The Media Coverage of the EU Referendum in Portugal, Isabel Simões-Ferreira -- 14. The 'Brexit' referendum in the Greek press: Preliminary findings from a pilot study, Giorgos Katsambekis -- 15. It's the economy, stupid: Coverage of the British EU referendum in Norway, Birgitte Kjos Fonn -- 16. Whose news? How the Canadian media covered Britain's EU Referendum, Christopher Waddell -- 17. The Media Coverage of the EU Referendum in Israel, Tal Samuel-Azran and Yair Galily -- 18. Brexit in the Russian Media,Helena Bassil-Morozow -- 19. Conclusion, Anthony Ridge-Newman,Fernando León-Solis, Hugh O'Donnell.
Literature, Cultural and Media Studies
text file PDF
Keywords: Communication; European Union; Ethnology-Europe.; Journalism